Almost Periodic Solution of a Discrete Schoener's Competition Model with Delays. (24th July 2014) - Zhang, Hui; Li, Yingqi; Jing, Bin; Fang, Xiaofeng; Wang, Jing
Abstract : We consider an almost periodic discrete Schoener's competition model with delays. By means of an almost periodic functional hull theory and constructing a suitable Lyapunov function, sufficient conditions are obtained for the existence of a unique strictly positive almost periodic solution which is globally attractive. An example together with numerical simulation indicates the feasibility of the main result.